2020
DOI: 10.1037/emo0000666
|View full text |Cite
|
Sign up to set email alerts
|

Relationship context and emotion regulation across the life span.

Abstract: A growing body of literature points to the important role that context plays in emotion regulation. One dimension of context that has significance for emotion regulation is the nature of the relationship between interactive partners. This review provides an organized account of existing empirical evidence assessing emotion regulation within close relationships across the life span. Specifically, the reviewed research includes studies examining parentϪchild relationships, sibling relationships, friendships, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…According to the second finding of the current study, individuals' use of emotional regulation strategies significantly and positively predicts their positive affect. This finding of the current study concurs with the existing research in the literature (Chiu et al, 2020;Ghorbani et al, 2020;Lindsey, 2020;Lopez & Denny, 2019;Southward & Cheavens, 2020;Vitale et al, 2018;Yosefi, 2015;Wante et. al., 2018).…”
Section: Discussionsupporting
confidence: 93%
“…According to the second finding of the current study, individuals' use of emotional regulation strategies significantly and positively predicts their positive affect. This finding of the current study concurs with the existing research in the literature (Chiu et al, 2020;Ghorbani et al, 2020;Lindsey, 2020;Lopez & Denny, 2019;Southward & Cheavens, 2020;Vitale et al, 2018;Yosefi, 2015;Wante et. al., 2018).…”
Section: Discussionsupporting
confidence: 93%
“…As per the current call for ER research on social and developmental factors (Barthel et al, 2018;Lindsey, 2020;McRae & Gross, 2020;Mikulincer & Shaver, 2019) this report focuses on internal representations of relationships (IRR). IRR are mental structures and tendencies, which develop through interactions between developmental experiences and dispositions (Blatt, 2004;Kernberg & Caligor, 2005).…”
Section: Individual Differences In Emotional Regulationmentioning
confidence: 99%
“…relationships) and developmental (e.g. age) factors (Barthel, Hay, Doan & Hofmann, 2018;McRae & Gross, 2020;Lindsey, 2020;Mikulincer & Shaver, 2019). Furthermore, there is a relative dearth of experimental ER research assessing neural dynamics in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout childhood, caregivers continue to play a key role in scaffolding the young child’s emotional experiences, guiding them toward the use of increasingly sophisticated and intentional regulatory strategies (Crugnola et al, 2013 ; Eisenberg et al, 1998 ; Gottman et al, 1996 ; Grabell et al, 2019 ; Lincoln et al, 2017 ; Morris et al, 2007 ; Thompson, 2014 ). Several studies have demonstrated that caregiver responses to children’s expressions of emotions shape how children learn to communicate about and manage their emotions (Lindsey, 2020 ; Perry et al, 2020 ; Shewark & Blandon, 2015 ). When parents respond supportively to children’s displays of emotions (e.g., validating, encouraging expression, soothing when needed), children are more comfortable experiencing and expressing a range of emotions–both positive and negative–and increasingly secure that such expressions do not compromise the relationship or run the risk of eliciting punitive or withdrawing responses from key caregivers.…”
Section: Introductionmentioning
confidence: 99%